Dynamic reflection coefficient Effect on the impact wave energy exchange and the strength of carriers (Damascus University Journal for engineering sciences, 2021)
The scientific basis for developing and improving the efficiency of impact machines to get the greatest amount of raw materials in the shortest time depends on three fundamental things related to the structure of the impact drill machine: First, the mass of the impactor, its engineering specifications and speed. Secondly, the multi-link wave carrier, and thirdly, the drill tool at the end of the wave carrier and its specifications.During the impact process at the onset of the wave carrier, an internal deformation wave (pressure stresses) is formed on a specific part of the carrier and propagates at the speed of sound in the wave carrier [1] through its repetitive and connected parts, taking with it the kinetic energy of the impactor to the place where it is to be invested, where the energy is exchanged with the raw materials.When the deformation (stress) wave passes between the sequential carriers, and the drilling tool head to the raw materials, part of the loaded energy in the deformation wave is dispersed during the transition, a part is invested in the drilling process and a part is reflected back to the drilling machine, without doing any useful work, this has a negative effect on the efficiency and durability of the machine, depending on the quality of the contact between carriers and the dynamic reflection coefficient between the drilling tool head , the raw materials and its dynamic resistance [1,2].This has been clarified by the study and analysis of mathematical equations which show the effect of clearances and dynamic reflection coefficient, when crossing bonds in carriers and exchanging energy with raw materials, on the wave's deformation, and the machine efficiency.  This research has shown the need to take into consideration the dynamic reflection coefficient and its effect on the durability and efficiency of the machine in order to avoid the aforementioned negative aspects.
Keywords: : Longitudinal impact; propagation of longitudinal waves; energy of shock waves; Dynamic machines; resistance of materials